An investigation on the pore pressure for the potential shale gas intervals in the Perth and Canning basins - Ahmad, Abualksim A (Curtin University, 2015)
This research examined various sets of data to examine pore pressure for the Potential Shale Gas Intervals in the Perth and Canning Basins, Western Australia. The study came up with an appropriate correlation between the existence and preservation of overpressure and the local tectonic and structural elements in the gas shale formations. This study has also assessed the suitability of the overpressure estimation method, examined the origins of overpressures wherever exist and improved the methodologies that were initially proposed by previous authors.